Using N-of-1 trials to improve patient management and save costs. - Scuffham, P; Nikles, J; Mitchell, G; Yelland, M; Vine, N; Poulos, C; Pillans, P; Bashford, G; del Mar, C; Schluter, P; Glasziou, P (2010)
BACKGROUND: N-of-1 trials test treatment effectiveness within an individual patient. OBJECTIVE: To assess (i) the impact of three different N-of-1 trials on both clinical and economic outcomes over 12 months and (ii) whether the use of N-of-1 trials to target patients' access to high-cost drugs might be cost-effective in Australia. DESIGN: Descriptive study of management change, persistence, and costs summarizing three N-of-1 trials. PARTICIPANTS: Volunteer patients with osteoarthritis, chronic neuropathic pain or ADHD whose optimal choice of treatment was uncertain. INTERVENTIONS: Double-blind cyclical alternative medications for the three conditions. MEASURES: Detailed resource use, treatment and health outcomes (response) data collected by postal and telephone surveys immediately before and after the trial and at 3, 6 and 12 months. Estimated costs to the Australian healthcare system for the pre-trial vs. 12 months post-trial. RESULTS: Participants persisting with the joint patient-doctor decision 12 months after trial completion were 32% for osteoarthritis, 45% for chronic neuropathic pain and 70% for the ADHD trials. Cost-offsets were obtained from reduced usage of non-optimal drugs, and reduced medical consultations. Drug costs increased for the chronic neuropathic pain and ADHD trials due to many patients being on either low-cost or no pharmaceuticals before the trial. CONCLUSIONS: N-of-1 trials are an effective method to identify optimal treatment in patients in whom disease management is uncertain. Using this evidence-based approach, patients and doctors tend to persist with optimal treatment resulting in cost-savings. N-of-1 trials are clinically acceptable and may be an effective way of rationally prescribing some expensive long-term medicines.